Le lien santé-travail au prisme de la prévention. Perspectives juridiques - Emmanuelle Lafuma; Cyril Wolmark (Perspectives Interdisciplinaires sur le Travail et la Santé)
The goal of this paper is to clarify the relation between work and health from the angle of the legal understanding of prevention. It also attempts to show the extent to which French law enables or promotes, by means of prevention, a debate about work. The field of criminal liability nonetheless remains impervious to debates on work organisation. The predetermined, detailed regulatory provisions are not conducive to discussions about work. At the same time, French law has been promoting, among worker representatives and health professionals, the conditions for internal company debates on prevention. That being said, this debate does not directly deal with the employers’ criminal or civil liability. However, in the field of civil liability, European case law’s recognition of the employer’s safety obligations has marked a decisive turning point. The employer’s obligation to analyse, reduce, and ultimately prevent occupational risks opens the door to discussions about the specific context of work.